Exposure to Heated Tobacco Products Aerosol Causes Acute Stress Responses in the Lung of Mouse - Shin Koike; Kohei Sato; Marie Sawa; Yohei Inaba; Kenji Hattori; Kazuhiko Nakadate; Akira Ushiyama; Yuki Ogasawara (MDPI AG, 2022)
In the present study, we evaluated the acute response of mice exposed to IQOS aerosol, a brand-name heated tobacco product (HTP), in the lung tissue. First, the thiobarbituric acid-reactive substances (TBA-RS) value was measured as an index to assess oxidative stress, and a significant increase was observed after exposure, followed by a significant increase in the total lung GSH concentration. The stress responses induced by IQOS aerosols was then analyzed by focusing on the changes in Nrf2 and ATF4, which are transcription factors that induce the expression of genes involved in GSH biosynthesis or metabolism. Although Nrf2 activation was not observed, significant accumulation of ATF4 in the nuclear fraction was noted three hours after exposure to IQOS aerosols. Upon an examination of changes in factors in the GSH biosynthetic system, a significant increase in cystine concentration in the lung tissue was measured, and an increase in xCT expression level was observed in the cell membrane fraction three-six hours after IQOS exposure. Furthermore, characteristic changes in HO-1, a stress-response protein regulated by ATF4, was discovered six hours after IQOS exposure. Moreover, analysis of the upstream ATF4 regulatory system revealed that phosphorylation of eIF2α was enhanced in the lung cytoplasmic fraction three hours after exposure to IQOS aerosols. These findings suggest that ER stress might be induced as an early response to IQOS aerosol exposure, accompanied by the activation of the eIF2α-ATF4 axis. These intracellular changes have also been reported after exposure to combustible cigarette smoke. Thus, the acute response found in the lungs of mice in the present study demonstrate that the inhalation of aerosols from IQOS elicits a biological response similar to that of combustible cigarette smoke. In conclusion, our results provide evidence that the biological effects of HTPs, such as IQOS, cannot be ignored in the lungs.